Morphology Behavior of Polysulfone Membranes Made from Sustainable Solvents - Steven Kluge; Karla Hartenauer; Murat Tutuş (Gases)
In a previous study, we demonstrated a change in membrane morphology and gas separation performance by varying the recipe of a casting solution based on polysulfone in a certain solvent system. Although all results were reproducible, all used solvents were harmful and not sustainable. In this study, the solvents tetrahydrofuran (THF) and N,N-dimethylacetamide (DMAc) are replaced by the more sustainable solvents 2-methyl-tetrahydrofuran (2M-THF), N-butyl pyrrolidinone (NBP) and cyclopentyl methyl ether (CPME). The gas permeation performance and, for the first time, morphology of the membranes before and after solvent replacement were determined and compared by single gas permeation measurements and SEM microscopy. It is shown that THF can be replaced by 2M-THF and NBP without decreasing the gas permeation performance. With CPME replacing THF, no membranes were formed. Systems with 2M-THF as a THF alternative showed the best gas permeation results. Permeances for the tested gases oxygen (O2), nitrogen (N2), carbon dioxide (CO2) and methane (CH4) were 5.91 × 10−2, 8.84 × 10−3, 4.00 × 10−1 and 1.00 × 10−2 GPU, respectively. Permselectivities of those membranes for the gas pairs O2/N2, CO2/N2 and CO2/CH4 were 6.7, 38.3 and 34.0, respectively. When also replacing DMAc in the solvent system, no or only porous membranes were obtained, even if the precipitation procedure was adjusted. These findings indicate that a complete replacement of the solvent system without affecting the membrane morphology or gas permeation performance is not possible. By varying the temperature of the precipitation bath, the formation of mechanically stable PSU membranes is possible only if THF is replaced by 2M-THF.